Peran Orang Tua Dalam Membentuk Motivasi Belajar Anak Di Usia Dini - Firmansyah, Fitri Awan Arif; Tyas, Devi Marganing (KOLONI, 2025)
This paper discusses the role of parents in improving children’s learning motivation. The children refered to in this paper are children of primary school age (SD/MI) is those aged 3 years to 6 years. Parents have of very important role in the education of their children among them as a motivator. In this case the parents should always give encouragement to their children to have a passion in learning, especially in home study as a supporter of successful achiement in school. The efforts that can be done by parents in improving motivation to learn children include: 1) knowing the results, 2) providing rewards and punishments, 3) provide the necessary tools or facilities. Parents as educators should always pay attention to child’s personal development as a determinant in the treatment of education in accordance with the period or level of age and ability to think chil